2009
DOI: 10.1111/j.1745-7599.2009.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐induced somatization in spouses of deployed and nondeployed servicemen

Abstract: Providers should be familiar with common somatic symptoms, treatments used for somatization and adjunct community resources available to patients with stress-related somatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…These fi ndings indicate that changes in psychological health secondary to stressors of deployment are prominent issues. Moreover, Burton, Farley, and Rhea (2009) found that increased levels of depression, anxiety, and stress are frequently associated with somatization for spouses. The top fi ve somatic complaints were feeling tired or having little energy, trouble sleeping, menstrual cramps and problems with the menstrual cycle, back pain, and heart palpitations.…”
Section: Research On Military Spousementioning
confidence: 97%
“…These fi ndings indicate that changes in psychological health secondary to stressors of deployment are prominent issues. Moreover, Burton, Farley, and Rhea (2009) found that increased levels of depression, anxiety, and stress are frequently associated with somatization for spouses. The top fi ve somatic complaints were feeling tired or having little energy, trouble sleeping, menstrual cramps and problems with the menstrual cycle, back pain, and heart palpitations.…”
Section: Research On Military Spousementioning
confidence: 97%
“…Many spouses have a difficult time coping with life during their spouse's deployment and managing the stress that ensues, and may not possess the ability to transition to a new way of life without the service member present (Lapp et al, 2010;Mansfield et al, 2010;Messecar & Kendall, 1998;Tollefson, 2008). There are several studies on the effects on spouses of active duty service members' deployments and multiple deployments (Burton, Farley, & Rhea, 2009;Eaton et al, 2008;Mansfield et al, 2010;SteelFisher, Zaslavsky, & Blendon, 2008), but there is limited knowledge on the effects of multiple deployments on spouses of National Guard (NG) service members.…”
mentioning
confidence: 96%
“…1,3 Increased stress during pregnancy has been associated with negative pregnancy outcomes such as preterm delivery and low birth weight, possibly secondary to release of stress hormones, which have a direct effect on uterine activity. [11][12][13][14][15][16][17] Anxiety and stress are postulated to increase the risk for postpartum depression. Our study found women in the deployed group had a threefold increased risk for postpartum depression in comparison with the nondeployed group after controlling for multiple confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Larger studies are needed to evaluate whether spouse deployment during pregnancy has other perinatal effects and whether group prenatal care may have a positive effect on adverse perinatal outcomes in this population. 11,2001, initiated the longest period of armed conflict for the United States, during which, over the past decade, more than 2 million members of the U.S. Armed Forces have been deployed to combat. 1 Military deployments have significant effects on the physical and mental health of American service members.…”
mentioning
confidence: 99%